(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the issue of family and family values ​​in the Uzbek-Korean literature of the XX century through analysis of stories. Furthermore, it explores writers’ skills in creating the image, views on the world and the person along with the problem of values.